Soil trace gas fluxes in living mulch and conventional agricultural systems. Issue 2 (9th March 2020) - Peters, Samuel J. W.; Saikawa, Eri; Markewitz, Daniel; Sutter, Lori; Avramov, Alexander; Sanders, Zachary P.; Yosen, Benjamin; Wakabayashi, Ken; Martin, Geoffrey; Andrews, Joshua S.; Hill, Nicholas S.
Abstract: Row crop agriculture is a significant source of two major greenhouse gases (GHGs) (carbon dioxide [CO2 ] and nitrous oxide [N2 O]) and the air pollutant precursor ammonia (NH3 ). Fluxes of these naturally occurring trace gases are often augmented by agricultural practices, such as fertilizer application and crop systems management. A living mulch system (LMS) maintains a live cover crop year‐round and is an emerging agricultural system that can reduce pesticide and fertilizer use while maintaining yields. Multiple trace gas fluxes of GHGs and NH3 had not previously been measured together in an LMS of corn ( Zea mays L.) and white clover ( Trifolium repens L.). This study compared soil gas fluxes in a white clover LMS with two other cover crop systems and a no‐cover‐crop system. Infrared and gas chromatography measurements were taken over 2 yr in northern Georgia. Mean soil CO2 and N2 O fluxes (159.7 kg ha −1 d −1 and 0.027 kg N ha −1 d −1, respectively) observed in LMS plots exceeded those from other treatments. Soil temperature, moisture, potentially mineralizable nitrogen (N), and nitrate partially explained these differences. Mean soil NH3 emissions were greater in LMS (0.089 kg N ha −1 d −1 ) compared with no cover crop (0.038 kg N ha −1 d −1 ). Increased N2 O and NH3 fluxes could be from release of N from decomposition of clover and from release of N into the soil as the corn shades the clover. Although LMS plots did not reduce trace gas emissions, labile carbon content was at least 100 mg kg −1 greater than other treatments after 2 yr, improving soil health.